Playing with real-time operating system (RTOS) micrium/OS-III - Min, Miaolin (2015)
A real-time operating system (RTOS) is an operating system (OS) intended to serve real-time application process data, typically without buffering delays. It plays an important role in time-critical systems, such as automative control system and visual inspection system. The operating system used in this project is called Micrium/OS-III. This paper discusses a project which applies the concepts of real-time operating system to robotics. In this project, two methods are introduced about how to search the target robot wirelessly. Method one uses single EVALBOT robot to locate the target robot alone, whereas in method two, two robots communicate wirelessly to locate the target robot together. The wireless protocol used was SimplitciTi, a low-power RF protocol.